Consumer Sentiment Analysis in Continuous Marketing - Asri Kunda; Sigit Sugiardi; Monica Feronica Bormasa; Asep Supriadi; Muliyati Muliyati (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The objective of this research is to examine consumer attitudes toward sustainable marketing practices in order to ascertain the efficacy of marketing strategies and to identify the challenges faced by companies in this regard. This study employed a qualitative approach, with data collected through in-depth interviews with 20 consumers and social media analysis to identify consumer sentiment patterns. The findings indicate that the majority of consumers hold positive attitudes toward sustainable marketing, particularly with regard to environmental awareness and the company's dedication to environmental preservation. However, the primary challenges identified include the perception of elevated prices on sustainable products and a lack of confidence in sustainability claims (greenwashing). The conclusion of this study underscores the significance of transparency and effective communication in sustainable marketing strategies to foster consumer trust. This research offers strategic insights for companies seeking to enhance sustainability campaigns and cultivate consumer loyalty.